PENJABARAN KOREKSI FISKAL PADA PAJAK PENGHASILAN PT. MERPATI TRAINING CENTER - Nabilah Karina Putri (2020)
PT. Merpati Training Center is a company engaged in the field of training and education services related to aviation. The company pays corporate income tax every year based on the percentage of the rate from the commercial profit report which is then adjusted according to the tax provisions to obtain fiscal profit. Calculation of commercial profits and fiscal profits can be different results. The analysis related to these differences needs to be elaborated, the purpose of which is to be able to elaborate on the calculation that occurs in positive and negative fiscal corrections that are adjusted to the tax laws and to find out the amount of income tax payable PT. Merpati Training Center in 2018. The results of the discussion showed a difference between commercial profits and fiscal profits. This happens because commercial financial statements are prepared based on financial accounting standards and fiscal financial reports are prepared based on taxation provisions. Fiscal corrections are needed to make adjustments to these differences. After making the translation related to fiscal correction, it can be known the cause of the revenue or expense is to be corrected, which is adjusted based on the applicable taxation provisions. And there are positive and negative corrections due to time differences and fixed differences where the correction will affect taxable income.